Herding and Feedback Trading by Institutional and Individual Investors - Nofsinger, John R.; Sias, Richard W. (Journal of Finance, 1999)
ABSTRACT We document strong positive correlation between changes in institutional ownership and returns measured over the same period. The result suggests that either institutional investors positive‐feedback trade more than individual investors or institutional herding impacts prices more than herding by individual investors. We find evidence that both factors play a role in explaining the relation. We find no evidence, however, of return mean‐reversion in the year following large changes in institutional ownership—stocks institutional investors purchase subsequently outperform those they sell. Moreover, institutional herding is positively correlated with lag returns and appears to be related to stock return momentum.